The Cantonese Hearing in Noise Test for Children - Wong, Lena L. N. (Trends Hear, 2019)
The aim of this study was to develop a children's version of the Cantonese Hearing in Noise Test (CHINT-C). This was accomplished in two stages. First, a total of 120 sentences understood by children aged 6-7 years were selected from the original pool of CHINT sentences and were grouped into 12 lists, each containing 10 sentences composed of 10 characters. Following this, 260 primary and secondary school children, with ages ranging from 6 to 17 years, and 21 adults of age 18 or older were administered the CHINT-C to determine its reliability/validity, normative data, and age-specific correction factors. The result showed good interlist reliability, and test–retest reliability for the CHINT-C. The speech perception skills assessed using the CHINT-C do not reach adult level until after 11-13 years of age. Correction factors were established that could be used to determine age-specific norms for the evaluation of speech intelligibility of children in various sound fields.